The Impact of Hand Grip and Sit-and-Reach Exercises in Children Aged 6 to 7 Years - Jiang Wen Ming; Ahmad Alhussin Alali; Nor Fazila Abd Malek; Nor Ikhmar Madarsa; Mohd Hafizuddin Baki; Nur Ikhwan Mohamad (Journal of Coaching and Sports Science, 2023)
It has been suggested that grip strength can predict physical fitness in children and adults. The overall plan of this study is to validate this conclusion. The study analyzed the correlation between hand grip strength and sit-and-reach in 70 children aged 6-7 years to gain insight into the correlation between grip strength and sit-and-reach. Descriptive statistics were used in the study to find out the mean scores and differences in these exercises. The correlation between hand grip strength and sit-and-reach flexibility was also explored using Pearson's correlation coefficient. The results showed the correlation coefficient between hand grip strength (mean±sd=5.46±3.75) and sit-and-reach flexibility (mean±sd=8.25±5.28) was 0.078, indicating a weak positive correlation (p more than 0.05). The study's results suggest that grip strength is not a valid predictor of physical dexterity in seated forward bends in the 6-7-year-old children age group. As suggested in previous studies, grip strength can predict physical fitness in children, such as a strong correlation between grip strength and physical flexibility, lung function, muscular endurance, and physical stability. However, from the results, grip strength is not a reliable predictor of physical flexibility. We need to validate further the predictive role of grip strength for other physical fitness indicators. This is a very important validation for us to develop children's physical fitness assessment programs more efficiently in the future.